Profitability, Stock Price Synchronicity, and Fraud: Implications for Earnings Management - Satria Amru Dito; Helisa Noviarty; Muhsin (Institut Bisnis dan Informatika Kesatuan, 2025)
The capital market is one of the main indicators of economic health, which is very sensitive to changes in global and domestic conditions. The aim is to analyze this moderating effect and provide insights into the risks associated with information transparency. Using a quantitative approach and secondary data from 35 technology firms listed on the Indonesia Stock Exchange (IDX) and Yahoo Finance, the data were analyzed through multiple linear regression and moderated regression analysis (MRA). Earning Management (EM) was measured using the Modified Jones Model, Stock Price Synchronicity (SPS) through the Morck et al. approach, Financial Statement Fraud (FSF) via the Beneish M-Score, and profitability using Return on Assets (ROA). The statistical results indicate that neither Stock Price Synchronicity nor Financial Statement Fraud had a significant effect on Earning Management. Moreover, profitability did not significantly moderate the relationship between Stock Price Synchronicity and Earning Management, nor between Financial Statement Fraud and Earning Management. The main findings suggest that, within the context of the sampled Indonesian technology firms, there is no empirical evidence supporting the influence of Stock Price Synchronicity and Financial Statement Fraud on Earning Management nor the moderating role of profitability, indicating the possible presence of other, more influential factors.